Analisis Pengaruh Pengembangan Sumber Daya Manusia dan Komitmen Organisasi terhadap Turnover Intention melalui Kepuasan Kerja - Wica Tiara; Kiki Farida Ferine; Muhammad Alfahmi (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study analyzes the influence of human resource development (HRD), organizational commitment, and job satisfaction on turnover intention at PT. Langtuhut Karya Medan, with job satisfaction as a mediator. The results show that HRD significantly affects job satisfaction, but it also positively contributes to turnover intention. In contrast, organizational commitment and job satisfaction have a significant negative relationship with turnover intention, indicating that increasing both can reduce employees' intention to leave. Furthermore, job satisfaction proves to be a significant mediator between HRD and turnover intention, as well as between organizational commitment and turnover intention. Based on these findings, the study suggests that the company should focus on improving job satisfaction, clarifying career development paths, and strengthening organizational commitment by enhancing employee welfare and providing appropriate rewards. Future research is recommended to explore additional variables such as work-life balance, transformational leadership, and organizational culture for deeper insights. Keywords: Human Resource Development, Organizational Commitment, Turnover Intention, Job Satisfaction, Pt Langtuhut Karya Medan.